Empowering Independence in Post-Mother Care at Home - Solikhah, Fitriana Kurniasari; Astuti, Erlina Suci (Inovasi Lokal, 2024)
The postpartum period is often also known as the puerperium period is defined as the time after placenta born and ended when tools?? content return like condition before pregnant . The postpartum period lasts during approximately 6 weeks. Objective activity This is For empowerment public especially Mother postpartum in maintenance self and care postpartum injuries in the work area Health Center Wagir , through stages : improvement? knowledge Mother postpartum about the post partum period , strengthening the support system ( family ) within accompanying the postpartum period mother and care postpartum wounds ( for? Mother sc or normal). Based on the implementation data of community service, the knowledge and practice scores of postpartum mothers before and after counseling increased by 51.62 points. The implementation of community service in the form of counseling and training in postpartum care at home, the intervention uses media in the form of modules, power point materials. Aids or media function to help and demonstrate something in the education or teaching process, the more senses are used to receive something, the more and clearer the knowledge or understanding obtained.